Gaya Interaksi Politikus Indonesia dalam Acara Talkshow di Televisi (Kajian Bahasa dan Gender) - Parwati Hadi Noorsanti; Hayatul Cholsy (Pusat Studi Wanita dan Keluarga UGM, 2023)
In verbal interactions, men and women usually speak in different ways, women tend to have a cooperative speech style, emphasize connection and intimacy, while men are individualistic and competitive. This research is qualitative research that aims to describe the speech styles used by three male and three female politicians in Indonesia in a talk show broadcast on television. The data in this study are the results of transcriptions of sentences spoken by politicians on the talk show. Data analysis was carried out by analyzing the features of conversation using the theory of female and male speech styles put forward by Holmes and Stubbe and Talbot. The results of this study concluded that male politicians and female politicians use male speaking style as the dominant speaking style, such as lecturing, reporting, referential-oriented, direct, problem solving, and independence. On the other hand, women's speaking styles that are also used by all male and female politicians are collaborative, connection-intimacy and supportive feedback.